Economic Development Problems In The Post-Pandemic World And Business Adaptation on The Example of A Chinese Company - Haijun Lu; Vladimir Grigoriev (Communications of International Proceedings, 2021)
The global spread of the coronavirus infection COVID-19 has led to a global recession and destabilized global financial markets. The fall in global GDP in 2020 was the largest since the Great Depression. The crisis is accompanied by a sharp increase in unemployment in a number of countries, significant sectoral effects, a decrease in investment activity, and a deterioration in the credit quality of borrowers and bank portfolios. The situation in the global financial markets, despite some stabilization, remains unstable. In these conditions, regulators around the world are implementing large-scale support measures (fiscal, monetary, financial) to limit the economic damage from the pandemic. The capital and liquidity buffers accumulated over the past decade in the financial system make it possible to implement countercyclical measures carried out by the state. But these may not be enough to quickly recover countries' global growth. Crisis trends may intensify if the pandemic drags on or new outbreaks occur. To date, only a small group of countries can overcome the crisis in 2021 in the event the coronavirus pandemic decays with the prospect of reaching sustainable GDP dynamics and high employment.
Keywords: Information Technology; Pandemic; Economics; Leasing; Financing; Leasing Portfolio.